A numerical solution of density distribution function of water adsorption sites on vacuum technical metal surfaces. (February 2017) - Li, Detian; Cheng, Yongjun; Li, Yanwu; Zhao, Lan; Sun, Wenjun; Wang, Yongjun
Abstract: During the pump-down process of technical metal vacuum systems without bakeout after air exposure, water makes up most of the desorbed gas in a short term. The desorbed water comes from the near-surface regions (inside the oxide layers and their surfaces) of the vacuum metal materials. If the thickness of the oxide layer is very small, and the surface is smooth, then the outgassing will be dominated by the mechanism of adsorption and desorption of water on the surface, and the molecular diffusion inside the oxide layer could be negligible. In some previous works, different isotherms were used to predict the pump-down curves, and to understand the mechanism of adsorption and desorption of water on the surfaces. The theoretical results with adjusted parameters often agreed well with the experimental phenomena. However, using these isotherms with known distributions to express the unknown densities of adsorption sites with different binding energies is an a priori method. In the present work, a numerical method is proposed to obtain a solution of density function of surface adsorption sites from the experimental data of pump-down reported by Edwards [J. Vac. Sci. Technol. 14, 606 (1977)]. Highlights: During pumpdown of vacuum system, water is dominated desorbed gas in a short term. A numerical method is proposed to obtain a solution of surface adsorption sites. Mechanism of adsorption and desorption of water on metal surface is investigated.